Pengaruh Pemberian Tablet Besi dan Vitamin C Terhadap Kadar Hemoglobin Mahasiswi S1 Keperawatan Universitas Muhammadiyah Surakarta - Kadafi, Muamar, Sulastri, S.Kp., M.Kes, Endang Zulaicha S., S.Kp, M.Kep (2015)
The low haemoglobin levels is one of health problems and often experienced for woman. If a woman with anemia, will influence for their activities, including student in study process. To increase levels of hemoglobin, its need a supplement is like iron tablet and vitamin c to become normal hemoglobin the purposes this study is to know influence of giving iron tablet and vitamin c to hemoglobin level of student of nursing program in Muhammadiyah University of Surakarta. the study is quasi research and pre-test post-test with control group. The sample was 55 students nursing program, which are divided into 25 as treatment group and 30 a control group. Instrument study with measurement of hemoglobin levels in pre test and post test, and give iron tablets for 30 days to treatment group. Data analysis was using paired test sample test and wilxocon test. The results of the study shows the average hemoglobin levels for treatment group in pre test was 10,66 gr % and post test become 11,11 gr %. The average hemoglobin levels for control group in pre test 10.59 gr % and post test with 10,52 gr %. Statistical testing at treatment group by test paired sample test obtained p = 0,001 ( p<; 0.05 ), so that it was concluded there is an influence of giving iron tablet and vitamin c to hemoglobin level of student of nursing program in Muhammadiyah University of Surakarta. Based on results of test Wilcoxon sign rank test for control group, obtained p = 0,425 ( p>; 0.05, so that it was concluded there is no difference hemoglobin level of student of nursing program in Muhammadiyah University of Surakarta between pre test and post test.